The Effects of Matcha on the Functioning of Selected Body Systems: A Literature Review - Sado, Aleksandra; Lisik, Bartłomiej; Kozieł-Kwit, Sylwia; Rogowska, Wiktoria; Szada-Borzyszkowski, Krzysztof; Sawczuk, Kacper; Simlat, Aleksandra; Skowierzak, Filip; Wręczycki, Mariusz; Kozyra, Klaudia (Journal of Education, Health and Sport, 2026)
Matcha, a powdered green tea originating from Japan, is a rich source of polyphenols, catechins, L-theanine, caffeine, vitamins, and minerals. This review summarizes current evidence regarding the potential effects of matcha consumption on selected physiological systems and overall human health. Available data suggest that regular intake of matcha may exert beneficial effects on the cardiovascular system and demonstrate antioxidant, anticancer, and neuroprotective properties, while also supporting stress reduction and cognitive function. However, the magnitude of these effects appears to depend on factors such as the quality of raw materials, cultivation conditions, and preparation methods. Although existing findings are promising, a substantial proportion of the available evidence originates from in vitro studies, animal models, and limited clinical trials, which restricts the strength of current conclusions. Therefore, matcha should be considered a complementary component of a healthy diet rather than a substitute for established preventive or therapeutic strategies. Further well-designed clinical studies involving larger populations and longer follow-up periods are required to more precisely determine its potential impact on human health.